Factors influencing integration of mental health screening and treatment at HIV clinic settings in Cameroon: a qualitative study of health providers' perspectives - Kathryn E. L. Grimes; Peter Vanes Ebasone; Anastase Dzudie; Denis Nash; Milton L Wainberg; Brian W. Pence; Clare Barrington; Eric Pefura; Marcel Yotebieng; Kathryn Anastos; Denis Nsame; Rogers Ajeh; et al. (BMC, 2024)
Abstract Background Mental disorders are common among people with HIV (PWH) and are associated with poor HIV outcomes. Despite high unmet mental health needs among PWH, use of evidence-based mental health screening and treatment protocols remains limited at HIV treatment facilities across low-resource settings. Integrating mental health services into HIV care can reduce this gap. This study's objective was to explore factors that influence integration of mental health screening and treatment into HIV clinics in Cameroon. Methods We analyzed 14 in-depth interviews with clinic staff supporting PWH at three urban HIV treatment clinics in Cameroon. Interviews focused on current processes, barriers and facilitators, and types of support needed to integrate mental health care into HIV care. Interviews were recorded and transcribed. French transcripts were translated into English. We used thematic analysis to identify factors that influence integration of mental health screening and treatment into HIV care in these settings. Ethical review boards in the United States and Cameroon approved this study. Results Respondents discussed a lack of standardized mental health screening processes in HIV treatment facilities and generally felt ill-equipped to conduct mental health screening. Low community awareness about mental disorders, mental health-related stigma, limited physical space, and high clinic volume affected providers' ability to screen clients for mental disorders. Providers indicated that better coordination and communication were needed to support client referral to mental health care. Despite these barriers, providers were motivated to screen clients for mental disorders and believed that mental health service provision could improve quality of HIV care and treatment outcomes. All providers interviewed said they would feel more confident screening for mental disorders with additional training and resources. Providers recommended community sensitization, training or hiring additional staff, improved coordination to manage referrals, and leadership buy-in at multiple levels of the health system to support sustainable integration of mental health screening and treatment into HIV clinics in Cameroon. Conclusions Providers reported enthusiasm to integrate mental health services into HIV care but need more support and training to do so in an effective and sustainable manner.